2009
DOI: 10.1007/s10658-008-9417-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of naturally occurring Erwinia amylovora strains lacking the common plasmid pEA29 and their detection with real-time PCR

Abstract: Erwinia amylovora, the causal agent of fire blight, carries the common plasmid pEA29 of 29 kb. To screen for occurrence of natural strains without plasmid pEA29, we applied PCR analysis with primers from the plasmid and the chromosomal ams region. In addition, a described TaqMan probe from pEA29 and newly designed primers from the amsregion were used for identification by real-time PCR. One strain isolated in Iran, one strain from Spain and two strains from Egypt lacked plasmid pEA29. From a recent screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…The exact sizes of the products can be calculated from the primer names in the second column of Table 2. The assays were done as described before (12). For qPCR with SYBR green, hot start Taq polymerase (Amplicon) was used.…”
Section: Methodsmentioning
confidence: 99%
“…The exact sizes of the products can be calculated from the primer names in the second column of Table 2. The assays were done as described before (12). For qPCR with SYBR green, hot start Taq polymerase (Amplicon) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Such a reaction may indicate an earlier acquisition of pEA29 from E. amylovora. By contrast, a few isolates of E. amylovora without this plasmid were found in Egypt, Iran, Spain and the USA (Carey et al 2011;Llop et al 2006;Mohammadi et al 2009). Also, it was found that another plasmid of approximately 65 kb (pEI70) present in one of these isolates, showed no homology with pEA29.…”
Section: Analysis Of Nucleic Acidsmentioning
confidence: 96%
“…From 1 ml overnight cultures in LB medium was taken, of which 10 ll of culture was lysed in 1 ml 0.1 % Tween 80 by heating for 20 min at 65°C, and 4 ll of these lysates were used as template in PCR. The master mix for the PCR assays has been described recently [28].…”
Section: Pcrmentioning
confidence: 99%